STRATEGI PEMASARAN PRODUK OLAHAN HASIL PETERNAKAN BAKSO GORENG PADA KELOMPOK WANITA TANI MELALUI DIGITAL MARKETING SYSTEM - M. Imam Fadhlurrahman Natsir; P. Tandi Balla; Muh. Irfan Aryawiguna (Unit Penelitian dan Pengabdian Masyarakat Politeknik Pembangunan Pertanian Gowa, 2020)
Animal farm is one of important sub-sector in the farming industry to produce animal-based protein in the development. In Indonesia, there are many food processing producers and industries, such as the meat-processing industry. Meatball is one of the examples of meat-based products. It is a typical meat-based dished that is very popular in the country. This study aims to identify the marketing strategy of fried meatball through digital marketing system by determining the segments (geographical and demographic), targeting (value, volume, product, price, promotion, and distribution), and positioning (STP). It also examines the business strategy using SWOT analysis. The fieldwork has been conducted from March to June at Al Barokah Shop, Somba Opu district, Gowa, Sulawesi Selatan. The research analysis used descriptive statistics. The location of the samples was determined by purposive sampling. From the study, it reached a 35,17% effectivity rate. From the SWOT analysis, it could be concluded that appropriate strategies are social media marketing, public market, and developing the product to be a partnership to increase productivity.